A 'naked-eye' ratiometric and NIR fluorescent detection for hydrogen sulphide with quick response and high selectivity for and its bioimaging. (June 2019) - Ma, Tao; Huo, Fangjun; Yin, Caixia
Abstract: Recently, the fluorescence detection of H2 S in biological systems has attracted the attention of many analytical chemists. However, most of H2 S probes showed shorter fluorescence emission (<600 nm) with fluorescence intensity change induced by H2 S, which has some disadvantages of shallower tissue penetration and bigger autofluorescence interference. Herein, we have rationally designed a near-infrared and ratiometric fluorescent probe (YC−1 ) for the detection of H2 S based on isophorone. The detection process can be monitored by naked-eye. Addition of H2 S, YC−1 showed that the emission ratios of fluorescence intensity at 540 and 660 nm (I540/I660) with an obvious enhancement from 0.05 to 13.3. Besides, the color of YC−1 changes from pink to yellow. As a probe for H2 S, YC−1 exhibited better selectivity, better sensitivity and lower detection limits (0.17 μM). Moreover, YC−1 showed lower toxicity to HepG−2 cells and can be used for cell imaging. Graphical abstract: Image 1 Highlights: 1. A novel ratiometric and near-infrared fluorescent probe for detecting H2S was developed. 2. The probe showed higher selectivity and lower detection limit (0.17 μM) for H2S monitored by naked-eye. 3. The probe can be used for monitoring exogenous and endogenous H2S in HepG-2 cells.